Do Intensified Police Controls Change Perceptions of Apprehension Probability: A Field Experiment - Terpstra, Bo L. (Crime & delinquency, 2020)
The perceived sanction risk is an essential element in the theory of deterrence to link criminal policy and criminal behavior. Previous research has not made clear how or even if individuals update their perceived sanction risk in response to changes in actual criminal policy. This study presents the first field experiment on the updating of the perceived probability of apprehension. On one location the police intensified moped traffic controls during a period of 6 months, while the control intensity on a comparable location remained unchanged. Difference-in-difference estimates reveal that the increased police activity caused an upward revision of the perceived probability of apprehension of offenses such as operating a mobile phone while driving or driving under the influence of alcohol.